PSXV-9 Effect of Forty-Eight Hours of Feed and Water Deprivation on the Performance of Grazing Nellore Heifers. (21st September 2022) - Abreu, Mateus José I; Cidrini, Iorrano A; Batista, Luis Henrique C; Ferreira, Igor M; Oliveira, Karla A; Sousa, Luciana M; de França, Matheus Queiroz S; Bisio, Gustavo Henrique M; Resende, Flávio D; Siqueira, Gustavo R
Abstract: The study was carried out to evaluate the effect of water and feed deprivation for 48 hours on the performance of grazing Nellore heifers. Nellore heifers [n = 24; 238±10 kg body weight (BW); 16±2 months old] were randomly distributed in the following treatments: (CONT) grazing animals with free access to pasture, water, and mineral mixture (n = 12); and (PRIV) animals maintained under equal grazing conditions; however, deprived of pasture, water, and mineral mixture for 48 hours (n = 12). The heifers were managed in pastures of Urochloa brizantha cv. Marandu from April to November 2021. The grazing method was continuous stocking with a fixed stocking rate. The experiment lasted 225 days, from d-14 to d-1 was considered the adaptation period and from d0 to d211 the evaluation period. From d0 to d2 the PRIV animals were kept in pens without access to food and water for 48 hours. As expected, heifers of both treatments reached d0 with similar BW and ADG (247 kg and 0.600 kg/day, respectively; P ≥ 0.642). At the final of deprivation period (d2) PRIV animals were 14.6% lighter than CONT (246 vs. 210 kg of BW; P < 0.001). From d2 to d12 the animals exhibited a partial compensatory gain (3.430 vs. 0.996 kg/day; P < 0.001), reducing the difference in BW between treatments to 4.7% (256 vs. 244 kg of BW; P = 0.019). However, after d12 it was observed that ADG was similar (P ≥ 0.384) and PRIV heifers were 12 kg of BW lighter than CONTs by the end of evaluation period (311 vs. 299; P = 0.042). We conclude that grazing Nellore heifers deprived of water and feed for 48 hours partially compensate for their BW loss but remain 12 kg lighter than non-deprived animals along the production cycle.